Verticillium dahliae’s Isochorismatase Hydrolase Is a Virulence Factor That Contributes to Interference With Potato’s Salicylate and Jasmonate Defense Signaling - Zhu, Xiaohan; Soliman, Atta; Islam, Md. R.; Adam, Lorne R.; Daayf, Fouad (Frontiers in Plant Science, 2017)
This study aimed to dissect the function of the Isochorismatase Hydrolase (ICSH1) gene in Verticillium dahliae’s pathogenesis on potato. VdICSH1 was up-regulated in V. dahliae after induction with extracts from potato tissues. Its expression increased more in response to root extracts than to leaf and stem extracts. However, such expression in response to root extracts was not significantly different in the highly and weakly aggressive isolates tested. During infection of detached potato leaves, VdICSH1 expression increased significantly in the highly aggressive isolate compared to the weakly aggressive one. We generated icsh1 mutants from a highly aggressive isolate of V. dahliae and compared their pathogenicity with that of the original wild-type strain. The analysis showed that this gene is required for full virulence of V. dahliae on potatoes. When we previously found differential accumulation of ICSH1 protein in favor of the highly aggressive isolate, as opposed to the weakly aggressive one, we had hypothesized that ICSH would interfere with the host’s defense SA-based signaling. Here, we measured the accumulation of both salicylic acid (SA) and jasmonic acid (JA) in potato plants inoculated with an icsh1 mutant in comparison with the wild-type strain. The higher accumulation of bound SA in response to the icsh1 mutant compared to the wild type confirms the hypothesis that ICSH1 interferes with SA. However, the different trends in SA and JA accumulation in potato in the roots and in the stems at the early infection stages compared to the leaves at later stages indicate that they are both associated to potato defenses against V. dahliae. The expression of members of the isochorismatase family in the icsh1 mutants compensate that of ICSH1 transcripts, but this compensation disappears in presence of the potato leaf extracts. This study indicates ICSH1’s involvement in V. dahliae’s pathogenicity and provides more insight into its alteration of the SA/JA defense signaling’s networking.